Determinant of customer loyalty in Malaysian takaful industry - Abu Hassan, Lailatul Faizah; Wan Jusoh, Wan Jamaliah; Hamid, Zarinah (Elsevier, 2014)
The Malaysian Takaful industry is considered a growing industry with significant progress and continues to play an important socioeconomic role within the economy. In the new global economy, service providers are competing to develop and retain customers through increased satisfaction and loyalty. To achieve this aim, customer knowledge has been increasingly recognized as a key strategy in managing customer relationships. Organizations sometimes are not aware of what actually goes on in a customer's mind. This study is aimed to investigate the factors influencing customer loyalty among Malaysian Takaful customers. It focuses on the relationships among customer relationship management, customer satisfaction and customer loyalty. The population of the study will consist of customers who have subscribed to the Islamic insurance products and services. Self-administered questionnaires are distributed to eight Takaful companies in Malaysia as a study setting for this study. Structural Equation Modeling (SEM) is applied to test the constructs’ relationships. It is expected that findings from this study will contribute to the existing literature to both theoretical and managerial approaches in order to better understand the pattern of customer knowledge management, customer relationship management and customer lifetime value, especially in Takaful industry settings.